2021
DOI: 10.3389/fmicb.2021.638830
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotic Bacilli in Developing Synbiotic Food: Challenges and Opportunities

Abstract: The human body is inhabited by a vast diversity of probiotic microorganisms that could positively affect human physiology. Besides, prebiotic food substances may induce symbiotic relationship among probiotic species through the successful establishment of commensal microbiota, whose connections with the host are multifaceted and multidirectional. As deliberated throughout this review, prebiotic and synbiotic foods contain the capability to stimulate numerous health characteristics in host organisms through var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…While these bacteria are frequently associated with dairy products, invertebrates, and craniate, they also form a significant part of human microbiota 2 . These species are known to stimulate immunomodulatory effects and evince belligerent traits against deleterious bacterial or fungal pathogens 3 5 . Specifically, a probiotic bacterium Lactobacillus plantarum displays diverse morphological phenotypes and a remarkable ability to acclimatize to external settings, qualify it for wide-ranging medicinal and industrial applications 5 .…”
Section: Introductionmentioning
confidence: 99%
“…While these bacteria are frequently associated with dairy products, invertebrates, and craniate, they also form a significant part of human microbiota 2 . These species are known to stimulate immunomodulatory effects and evince belligerent traits against deleterious bacterial or fungal pathogens 3 5 . Specifically, a probiotic bacterium Lactobacillus plantarum displays diverse morphological phenotypes and a remarkable ability to acclimatize to external settings, qualify it for wide-ranging medicinal and industrial applications 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In line with these results, interesting properties and uses are specifically described for Bacillus spp. Recently, several Bacilli strains have been extensively proposed for use as human and animal probiotics [ 55 , 56 ]. Most of the species used belong to Bacillus subtilis and Bacillus amyloliquefaciens groups and special attention should be paid to the food and clinical studies with strains that showed special enzyme capacities [ 57 ] or those able to modulate and mitigate pathophysiological disorders [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The richness in micro-and macronutrients composition of chickpea legumes, including proteins, carbohydrates, and lipids, may provide an excellent medium for the growth of microorganisms [5,12,13]. The legume is often used to produce chickpea milk (CPM), a plant-based alternative for milk of mammalian origin.…”
Section: Discussionmentioning
confidence: 99%
“…In the right amounts, it confers health benefits to the host organism. These benefits include restoring or augmenting the healthy microflora [5], inhibiting the growth of pathogenic bacteria [6], and releasing by-products that the host organism can use for metabolic activities [7]. Most of the probiotic species are often sourced from dairy foods [8].…”
Section: Introductionmentioning
confidence: 99%